2013
DOI: 10.1111/iwj.12196
|View full text |Cite
|
Sign up to set email alerts
|

Avocado/soybean unsaponifiables: a novel regulator of cutaneous wound healing, modelling and remodelling

Abstract: We investigated the effects of avocado/soybean unsaponifiables (ASU) on the healing response of cutaneous wound defect in rats. Sixty male rats were randomly divided into three groups including control, vehicle and treatment (n = 20 in each group). A 2 × 2 cm(2) wound defect was made on the dorsum. The control, vehicle and treatment groups were treated daily with topical application of saline, cream and cream/ASU for 10 days, respectively. The wounds were monitored daily. The animals were euthanised at 10, 20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 33 publications
2
19
0
Order By: Relevance
“…It was reported that IGF-1 increases fibroblast cells in in vitro assessment (Lisa et al 2011). Improving cellular proliferation and differentiation are essential for shortening the healing time (Oryan et al 2015;Karimzadeh and Farahpour 2017). Proliferative effect of ZMEO is partly owing to its antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that IGF-1 increases fibroblast cells in in vitro assessment (Lisa et al 2011). Improving cellular proliferation and differentiation are essential for shortening the healing time (Oryan et al 2015;Karimzadeh and Farahpour 2017). Proliferative effect of ZMEO is partly owing to its antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid cellular proliferation and differentiation are necessary in shortening the healing time (Oryan et al. 2015; Karimzadeh and Farahpour 2017). Controlled apoptosis and up-regulated revascularization are associated with the increase in collagen deposition which accelerates the healing process (Wu and Chen 2014; Manzuoerh et al.…”
Section: Discussionmentioning
confidence: 99%
“…The study found that treatment (cream plus ASU) produced a significantly higher level of tissue glycosaminoglycan and collagen contents compared to controls. It was also reported that the treatment had a modulating effect on inflammation, improved fibroplasia and provided higher amounts of scar tissue; so, it was concluded that ASU is a promising agent in wound healing [115].…”
Section: Other Pharmacotherapeutic Uses Of Asumentioning
confidence: 99%